Eosinophilia – associated basal plasmacytosis: an early and sensitive histologic feature of inflammatory bowel disease. Issue 3 (25th January 2017) - Canavese, Gabriella; Villanacci, Vincenzo; Antonelli, Elisabetta; Cadei, Moris; Sapino, Anna; Rocca, Rodolfo; Daperno, Marco; Suriani, Renzo; Di santo, Maria Giulia; Cassoni, Paola; Bernardini, Nunzia; Bassotti, Gabrio
Abstract : Basal plasmacytosis is an early‐onset and highly predictive feature of inflammatory bowel disease (IBD), but may have several restrictions in routine histology. Considering evidences about cooperation between eosinophils and plasma cells in IBD pathogenesis, we investigated immunostain of these two cells as a marker of disease. 343 samplings from 83 patients (52 IBD, 31 non‐IBD colitis) were evaluated. The sections were stained with monoclonal antibodies against plasma cells (CD138 and MUM1), and eosinophils (CD193). Eosinophilia‐associated basal plasmacytosis (EBP) was related with the histologic diagnosis of IBD (90.3% IBD and 35.4% non‐IBD colitides, p < 0.005, sensitivity 90.4%). A strong relation was detected between the occurrence of EBP and (i) the achieving of a complete endoscopic mapping; (ii) the presence of other characteristic lesions of IBD in single segmental sampling, although EBP was evident in more than 40% of samples without other IBD‐related lesions. EBP is a sensitive histologic feature of IBD, especially at the first endoscopic sampling, even in the absence of the other characteristic histologic lesions, and may help in formulating a more precise diagnosis in this setting.